1975
DOI: 10.1055/s-0028-1093721
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Biosynthesis in Human Pancreatic Islets: Preliminary Evidence for a Biosynthetic Intermediate

Abstract: Viable pancreatic islets were isolated from the pancreas of humans using modifications of the collagenase digestion and Ficoll gradient techniques. Gel filtration of tissue extracts following islet incubation in the presence of 3H-tryptophan indicated that radioactivity becomes incorporated into at least two islet pro teins. The larger of the two (LGI) has the approximate molecular size of proinsulin and the sm aller coelutes with glucagon as determined by column standardization. Radioimmunoassay of the gel fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The 9,000 mol wt IRG in CRF plasma resembles material which is present in the pancreas of man and animals and which is now believed to be proglucagon (9)(10)(11)(12)(13)(14). Our studies lend support to the possibility that this circulating material might be proglucagon because exposure to trypsin converted it to small molecular weight components, some of which were similar in size to the native hormone.…”
Section: Isupporting
confidence: 67%
See 1 more Smart Citation
“…The 9,000 mol wt IRG in CRF plasma resembles material which is present in the pancreas of man and animals and which is now believed to be proglucagon (9)(10)(11)(12)(13)(14). Our studies lend support to the possibility that this circulating material might be proglucagon because exposure to trypsin converted it to small molecular weight components, some of which were similar in size to the native hormone.…”
Section: Isupporting
confidence: 67%
“…In a preliminary communication (7) we have shown that circulating IRG in this condition is heterogenous, and that a significant amount of glucagon immunoreactivity is present in a peak with a molecular weight of approximately 9,000, consistent with descriptions of proglucagon (8)(9)(10)(11)(12)(13)(14). Studies by other investigators have indicated that IRG may exist in several forms in plasma of normal and diabetic subjects (15,16) and of experimental animals (17,18).…”
Section: Introductionmentioning
confidence: 54%
“…The suggestion that this void volume material is secreted (Table III) cursor has not been conclusively proven, there is persuasive evidence that a larger molecule (or molecules) is sequentially cleaved to glucagon (14). Studies in islet tissue from a number of species including humans (14)(15)(16)(17) indicate that [3H]tryptophane is incorporated into a peptide of about 9,000 daltons. In addition, material of this weight with glucagon immunoreactivity has been found in pancreatic extracts from several species (10).…”
Section: Patientsmentioning
confidence: 99%
“…In addition to 3,500-dalton IRG, humani plasnma contains variable amounts of 160,000-and 9,000-dalton IRG, with elevated levels of the latter being common in patients with chroniic renal failure (8,22) and in those with glucagononmas (23)(24)(25)(26). Studies with human islets have demonstrated the inicorporation of [3H]tryptophan into both 9,000-and 3,500-dalton IRG (10). In the pedigree reported here, all affected familv members had excessive levels of L-IRG with molecular weights of 9,000 and 10,000-20,000 daltons.…”
Section: Resultsmentioning
confidence: 99%
“…The L-IRG in affected members consists of species with mol wt 9,000 and approximately 10,000-20,000 daltons, which are similar to the molecular weight of the putative precursors of 3,500-dalton glucagon which have been observed in human and animal in vitro pancreas studies (9,10). In addition, plasma levels of these L-IRG species IAbbreviations used in this paper: IRG, immunoreactive glucagon; L-IRG, large molecular weight immunoreactive glucagon; S-IRG, small molecular weight immunoreactive glucagon.…”
Section: Introductionmentioning
confidence: 99%